Vigabatrin-Induced Encephalopathy in a 5.5-Month-Old Girl with Infantile Spasms due to Tuberous Sclerosis - Eleni Klinaki; Ioanna Argyri; Georgia Amountza; Gerina Ioannidou; Despoina Maritsi; Anastasia Garoufi; George Vartzelis (Hindawi Limited, 2019)
A 5.5-month-old female infant with tuberous sclerosis complex presented with infantile spasms and was treated with vigabatrin. As her condition did not improve, she was given adrenocorticotropic hormone (ACTH) intramuscularly which stopped the spasms and improved the electroencephalogram (EEG) abnormalities. However, she developed encephalopathy with apathy, drowsiness, and generalized slowing in the EEG. Discontinuation of vigabatrin quickly improved her symptoms and reversed the EEG slowing. A high index of suspicion is required in order to diagnose vigabatrin-induced encephalopathy, especially as the underlying disorders of these patients can be erroneously considered the cause of the observed encephalopathy.